Interleukin-31 new biomarker of infectious skin diseases - Dorosh, Diana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. The introduction of antiretroviral therapy has significantly improved the long-term prognosis of AIDS patients, but opportunistic infections can still be life-threatening for this population. Among them, a large group constitutes of herpesvirus infections, which are frequent manifest forms of dermatological manifestations of HIV. The researching of IL-31, as a prospective diagnostic predictor of dermatological diseases, has been actively conducted in recent years. This is due to the interest in its biological action, which extends primarily to the skin. Тhe identification of molecular targets underlying inflammatory and infectious dermatoses is promisingly for the development of new, targeted treatments. Objective: to study the role of IL-31 in the immunopathogenesis of herpesvirus infections associated with HIV infection. Research objectives: 1) to compare the levels of IL-31 in the blood serum in patients with herpesvirus skin diseases associated with HIV infection and in healthy subjects; 2) to determine the presence of a relationship between the levels of IL-31 in the blood serum and the clinical stage of the disease. Materials and methods. The study included patients with herpesvirus infection caused by HSV-1, HSV-2, VZV-3, EBV and HHV-8 associated with HIV infection and healthy individuals. Serum IL-31 levels were measured by ELISA using commercial kits (Human IL-31 ELISA Kit, Abcam, Cambridge, MA, USA). Were collected the baseline clinical characteristics, assessment of the activity of the infectious process and the degree of immunosuppression. Results. Our study involved 39 patients with herpesvirus infection associated HIV and 31 patients of the control group. In patients with herpesvirus infection against the background of HIV infection, the average level of IL-31 in the blood serum was significantly higher than that of healthy subjects. Serum IL-31 levels in patients with herpesvirus infection did not differ significantly depending on the severity of the process and the degree of immunosuppression. Conclusion. The levels of IL-31 in the blood serum of patients with herpesvirus infection were differed by statistically significant validity in comparison with similar indicators of healthy individuals, which confirms its role in the pathogenesis of infectious skin diseases.